Parametric Study of the Intermediate External Bracing System of Composite Steel Box Girder Bridges - Malik, Hawraa Sami; Jawad, David A. M. (Basrah Journal for Engineering Sciences, 2021)
During the pouring of concrete deck, the installation of external bracing between the inner and outer girders may be necessary when the bridge has sharp curve in order to control the deflection and rotation of the girders. However, it is important to minimize the number of external bracing members, as they have expensive cost and they also have opposite effects for the fatigue features of the steel tub girders. The analysis of curved box girder bridges is carried out numerically by the use of finite element method through (ANSYS 19.2) software. The curved box girder with the intermediate external diaphragms was modeled and the analysis was carried out for many parameters like external bracing sections, girders with or without concrete deck, girders with end diaphragms or without them. The study concluded that ANSYS program has a good ability in evaluating the external bracing force comparing with code equations.